Inequality in educational opportunities and outcomes: Evidence From Young Lives data in Vietnam - Le Thuc, D; Nguyen Thi Thu, H (Young Lives, 2016)
This paper utilises Young Lives longitudinal data on two cohorts of 3,000 children in Vietnam, as well as a wealth of official Government data, to present a broad picture of the education sector in the country, focusing on inequality. For most of the period under study, Vietnam was a low-income country, but people always placed a high value on education. The evidence for the strong commitment includes the fact that the government has made changes in education policy quite frequently over the last 15 years, and public expenditure on education has increased as a percentage of GDP. From the private sector, the commitment is evident from the significant demand for extra classes, which are an unofficial supplement to the regular classes which occur mostly in public schools. An important achievement is that the country has reached the goal of universalisation of primary education, and has almost done so for basic education in general. Moreover, the gender gap in education is moderate in Vietnam, compared to other countries.